Anthropometric intraoperative measurement of the patella dimensions in total knee arthroplasty of female patients - Termizi, Nur Syahida Mohd (2018)
Background: Patellofemoral joint is considered as a complex joint involving articulation between the patella and femoral trochlea. Loss of patella articular cartilage occurs in patellofemoral arthritis that may require patella arthroplasty in Total Knee Arthroplasty (TKA). Proper patella implant sizing is important to prevent implant failure. However implants used for TKA in Asian patients mostly produced based on anthropometry of the Western population. We conducted this study to define intra-operative anatomy of patella dimensions in our populations and compare it with current prosthetic systems. Methods: This was a cross sectional study involving female patients who underwent Total Knee Arthroplasty in HUSM. Intra-operative anatomic measurements of 78 patellae with normal underlying bony structure were studied. Patella was measured using a surgical caliper which had sensitivity up to 0.5 mm. Patella dimensions that were measured including the patella height, width, thickness, medial and lateral articular facets width and thickness and patella circumference. Smallest implant size from 3 manufacturers were measured. Analysis using descriptive statistics was used to get the mean and median of anatomical patella dimensions, whereas Independent T test and One- Way ANOVA test were used to compare the female Malaysian patella dimensions with current prosthesis system sizing. Results: The articular surface of the patella was found to have an oval shape with a width-height ratio of 1.31. The mean patella thickness, width and height were 20.7 mm, 40.7 mm and 31.3 mm respectively. Only 17.9% fit for smallest implant size from all 3 companies while 57.6% did not fit for all implants. Oval-shape implant was suitable in 53.8% patients while another 46.2% were suitable for round-shape implant based on their width-height ratio. Conclusions: Our female patients have thinner and smaller patella which accommodate smaller patellar components than the Westerners. Therefore, the orthopaedic implant manufacturers have to consider optimizing the thicknesses as well as widths of their patellar prostheses.